Charles Darwin's On the origin of species - Stefoff, Rebecca, 1951- (Atheneum Books for Young Readers, 2018)
Presents a child-friendly adaptation of Charles Darwin's groundbreaking treatise highlighting his theory of evolution. Includes a glossary and color photographs.